Polyhydroxybutyrate production from ultrasound-aided alkaline pretreated finger millet straw using Bacillus megaterium strain CAM12. (April 2021) - Silambarasan, Sivagnanam; Logeswari, Peter; Sivaramakrishnan, Ramachandran; Pugazhendhi, Arivalagan; Kamaraj, Balu; Ruiz, Antonieta; Ramadoss, Govindarajan; Cornejo, Pablo
Graphical abstract: Highlights: Ultrasound aided NaOH pretreatment showed a greater delignification and sugar yield. Pretreated finger millet straw used for Polyhydroxybutyrate (PHB) production. Strain CAM12 produced 8.31 g L −1 of PHB in finger millet straw hydrolysates. Structural characterizations ensured the extracted biopolymer was PHB. Abstract: In this study, finger millet straw (FMS) was utilized for the production of Polyhydroxybutyrate (PHB) by Bacillus megaterium strain CAM12. Ultrasound-assisted alkaline (NaOH) pretreatment of FMS under optimized conditions followed by enzymatic saccharification resulted in the maximum delignification (72%), hydrolysis yield (84%), glucose yield (86%) and xylose yield (61%). The effects of different pH, temperature, incubation period, inoculum concentration, agitation speed and FMS enzymatic hydrolysates concentration were investigated to improve the PHB production. Under optimized conditions, strain CAM12 used the FMS hydrolysates as the sole carbon source for their growth and produced 8.31 g L −1 of PHB. The extracted polymer on Fourier transform infrared (FTIR), X-ray diffraction (XRD) and Nuclear magnetic resonance (NMR) analyses were confirmed to be PHB. These results suggest the potential of combined ultrasound and alkaline pretreated FMS hydrolysates as a promising feedstock for PHB production.